Foliar δ13C Showed No Altitudinal Trend in an Arid Region and Atmospheric Pressure Exerted a Negative Effect on Plant δ13C - Chen, Zixun; Wang, Guoan; Jia, Yufu (Frontiers in Plant Science, 2017)
Most previous studies have suggested that foliar δ13C generally increases with altitude. However, some studies reported no changes or even decreased trends in foliar δ13C with elevation. We noted that all the studies in which foliar δ13C increased with elevation were conducted in the humid regions, whereas those investigations in which foliar δ13C did not vary or decreased were conducted in areas with water stress. Thus, we hypothesize that the pattern of increasing foliar 13C with elevation is not a general one, and that foliar 13C may remain unchanged or decrease in plants grown in arid environments. To test the hypothesis, we sampled plants growing on shady and sunny slopes along an altitudinal gradient characterized by arid and semiarid climates on Mount Tianshan. The measurements of foliar δ13C showed no altitudinal trend for the plants grown on both slopes. Therefore, this study supports our hypothesis, and suggests that altitudinal variations in plant 13C depend on soil moisture content. The reason leading to no altitudinal foliar δ13C trend was that moisture also played a role in the altitudinal variations in foliar δ13C in study region. In addition, the present study also addressed the effect of atmospheric pressure on foliar δ13C by accounting for the effects of temperature and precipitation. This study found that the residual foliar δ13C increased with increasing altitude, suggesting that atmospheric pressure played a negative role in foliar δ13C.